2016
DOI: 10.3389/fpls.2016.01710
|View full text |Cite
|
Sign up to set email alerts
|

Strong Coupling of Shoot Assimilation and Soil Respiration during Drought and Recovery Periods in Beech As Indicated by Natural Abundance δ13C Measurements

Abstract: Drought down-regulates above- and belowground carbon fluxes, however, the resilience of trees to drought will also depend on the speed and magnitude of recovery of these above- and belowground fluxes after re-wetting. Carbon isotope composition of above- and belowground carbon fluxes at natural abundance provides a methodological approach to study the coupling between photosynthesis and soil respiration (SR) under conditions (such as drought) that influence photosynthetic carbon isotope discrimination. In turn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
20
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 49 publications
2
20
0
Order By: Relevance
“…When drought becomes more intense, carbohydrate transport in the phloem can be expected to decrease as typically both the source (photosynthesis) and at least part of the sink (growth and respiration) activity rates decrease (Blessing et al 2016;Hagedorn et al 2016). Since photosynthesis can be maintained when drought is intense enough for growth to stop (Pantin et al 2013;Klein et al 2014), a sink-limited slowdown of transport under drought is likely to occur (Lemoine et al 2013).…”
Section: How Does Drought Affect Phloem Transport?mentioning
confidence: 99%
“…When drought becomes more intense, carbohydrate transport in the phloem can be expected to decrease as typically both the source (photosynthesis) and at least part of the sink (growth and respiration) activity rates decrease (Blessing et al 2016;Hagedorn et al 2016). Since photosynthesis can be maintained when drought is intense enough for growth to stop (Pantin et al 2013;Klein et al 2014), a sink-limited slowdown of transport under drought is likely to occur (Lemoine et al 2013).…”
Section: How Does Drought Affect Phloem Transport?mentioning
confidence: 99%
“…Tight coupling between below‐ground autotrophic respiration and the availability of recently assimilated carbon (C) has become a paradigm in the ecophysiological literature (Högberg et al ., , ; Högberg & Read, ; Kuzyakov & Gavrichkova, ; Epron et al ., ; Blessing et al ., ). Substantial evidence supporting this paradigm comes from studies that have interrupted the transport of recently assimilated carbohydrates to the root system via stem girdling, a technique that severs phloem.…”
Section: Introductionmentioning
confidence: 97%
“…In contrast to the vast number of studies reporting instantaneous tree responses to drought, little is known about recovery from this environmental stress, even though this ability is an important factor determining the drought resistance of trees on a longer time scale. A few studies have considered the photosynthetic response of saplings exposed to cycles of drought and re-watering ( Tognetti et al, 1995 ; Gallé and Feller, 2007 ; Arend et al, 2013 , 2016b ; Blessing et al, 2016 ), while others have focused on the year-to-year variation in tree-ring growth in adult trees caused by annual fluctuations in precipitation ( Dittmar et al, 2003 ; Pretzsch and Dieler, 2011 ). Findings from these studies have demonstrated the ability of beech to resume physiological activity, particularly photosynthesis, and growth after severe drought, but the processes occurring after stress release remain poorly understood.…”
Section: Introductionmentioning
confidence: 99%